Survey to improve accessibility for person with disabilities - D, Manivannan; N.K, Manikandan; Kumar K, Kishore (International Journal of Engineering and Technology, 2018)
Accessibility is a concept that cuts across disciplines and refers to the design of products, devices, services, or environments for Persons with Disabilities (PwDs). A central feature of the rights-based approach to disability, accessibility as a concept emphasizes the role that society, the built environment and societal attitudes play in making PwDs feel disabled and places the onus of securing the rights of PwDs on the state. The recognition of the role that the state must play in securing the rights of PwDs has led to the near universal adoption of the United Nations Convention on the Rights of Persons with Disabilities (UNCRPD) and in turn, has led to a number of changes in the policies of state parties